2017
DOI: 10.1016/j.carbon.2017.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Unusual interconnected graphitized carbon nanosheets as the electrode of high-rate ionic liquid-based supercapacitor

Abstract: A type of unusual interconnected graphitized carbon nanosheets (GCNS) was fabricated from biomass waste, i.e., inner shaddock skins using a facile combined method of simultaneous carbonization-activation and post-vacuum-annealing processes. The obtained GCNS has an optimized integration of a cage-like high-aspect-ratio nanosheet structure (~8 nm thickness), a large surface area of 2327 m 2 g -1 and hierarchical meso/micropore systems (82.3% mesopore volume).Given the effect of post-vacuum-annealing process, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 51 publications
(95 reference statements)
2
41
0
Order By: Relevance
“…[ 30c ] Compared to the amorphous porous carbon skeleton (Figure 12h), ordered graphitic carbon shells (Figure 12i) formed around Co, which were responsible for the enhanced catalytic activity of porous carbon in degradation of HBA and phenol by AOPs (Figure 12j). In another example, under simultaneous FeCl 3 catalysis and ZnCl 2 activation at high temperature, interconnected graphitized porous carbon nanosheets were prepared from shaddock skins, [ 265 ] which integrated a high SSA (2327 m 2 g −1 ), cage‐like high‐aspect‐ratio nanosheet structure, abundant mesopore (82.3%) with some micropores. The high graphitization degree greatly enhanced electronic/ionic‐transport kinetics, which boosted excellent rate capability and high energy‐power property in supercapacitor tests.…”
Section: Hierarchically Porous Carbon Nanostructurementioning
confidence: 99%
“…[ 30c ] Compared to the amorphous porous carbon skeleton (Figure 12h), ordered graphitic carbon shells (Figure 12i) formed around Co, which were responsible for the enhanced catalytic activity of porous carbon in degradation of HBA and phenol by AOPs (Figure 12j). In another example, under simultaneous FeCl 3 catalysis and ZnCl 2 activation at high temperature, interconnected graphitized porous carbon nanosheets were prepared from shaddock skins, [ 265 ] which integrated a high SSA (2327 m 2 g −1 ), cage‐like high‐aspect‐ratio nanosheet structure, abundant mesopore (82.3%) with some micropores. The high graphitization degree greatly enhanced electronic/ionic‐transport kinetics, which boosted excellent rate capability and high energy‐power property in supercapacitor tests.…”
Section: Hierarchically Porous Carbon Nanostructurementioning
confidence: 99%
“…SEM/TEM images and cyclic voltammetry of biomass‐derived carbons for supercapacitors: a–c) self‐activated porous carbon . Copyright 2017, Wiley; d–f) hierarchical porous carbon . Copyright 2017, Elsevier; g–i) mesopore‐dominant hierarchical porous carbon .…”
Section: Biomass‐derived Carbon Materials For Supercapacitor Electrodesmentioning
confidence: 99%
“…Additionally, during the electrode fabrication process their re-stacking or aggregation has also greatly hindered their further applications. Surprisingly, some researchers are successful for preparing graphene-like sheets by using biomass (starch [85], wheat straw [26,86], hemp [87], coconut shell [88], inner shaddock skins [89]) as carbon source. As an example, Chen et al [86] developed high-quality graphene sheets with ultrathin nanosheet frameworks (2-10 atomic layers) and graphite-like interlayer spacing (0.3362 nm) from wheat straw via combining hydrothermal and graphitization (Fig.…”
Section: Tubular Structurementioning
confidence: 99%
“…As an example, Sun et al [88] have reported carbon nanosheets synthesized by waste coconut shell by metal salts simultaneous activation-graphitization. Recently, Tian et al [89] have also reported numerous interconnected carbon nanosheets with graphene-like structures fabricated from inner shaddock skins by simultaneous carbonization, ZnCl 2 activation and FeCl 3 catalysis. In the process of biomass turning into chars, a rapid contraction occurred in all the dimensions of the chars, leading to the generation of the thinner nanosheet structures.…”
Section: Tubular Structurementioning
confidence: 99%
See 1 more Smart Citation